Technics and Praxis - Ihde, D. author. aut Link
XXVIII, 163 p.
Keywords: Depending on how one construes the kinship relations, technology has been either the stepchild of philosophy or its grandfather. In either case, technology has not been taken into the bosom of the family, but has had to wait for attention, care and feeding, while the more unclear elements - science, art, politics, ethics - were being nurtured (or cleaned up). Don Ihde puts technology in the middle of things, and develops a philosophy of technology that is at once distinctive, revealing and thought provoking. Typically, philosophy of technology has existed at, or beyond, the margins of the philosophy of science, and therefore the question of technology has come to be posed (when it is) either by historians of technology or by social critics. The philosophy of technology, as analysis and critique of the concepts, methodologies, implicit epistemologies and ontologies of technological praxis and thought, has remained underdeveloped. When philosophy does turn its attention to the insistent presence of technology, it inevitably casts the question in one or another of the dominant modes of philosophical interpretation and reconstruction. Thus, the logic of technological thinking and practice has been a subject of some systematic work (e. g. , in the Praxiology of Kotarbinski and Kotarbinska, among others). And the question of technology's relation to science has been posed in the framework of the nomological model of explanation in the sciences - e. g.